Factors Affecting Scientific Attitude of IX Grade Students - Misra, K.S.; Srivastava, Stuti (INDIAN EDUCATIONAL REVIEW, 2016)
The present study examined the scientific attitude of IX grade students in relation to their scientific interest, science achievement, intelligence and personality. Sample comprised of 600 students of IX grade students studying in UP board schools in Allahabad city. Scientific attitude questionnaire, scientific interest inventory, general mental ability test, neo-personality questionnaire by K.S. Misra and self-constructed science achievement test (form A) were used to collect data. It was found that scientific attitude in intent as well in action is positively related to scientific interest. Scientific attitude in action is positively related to achievement in science. Scientific attitude in intent and action is not related to intelligence. Scientific attitude in intent and action is positively related to four personality traits namely—planned, inquisitive, motivated and adaptable. Scientific attitude in intent is positively related to two traits namely—analytical and tolerant and negatively related to one trait–pessimist but scientific attitude in action is not related to these personality traits. Scientific attitude in action is positively related to three traits namely-self-sufficient, sociable, independent and divergent but scientific attitude in intent is not related to these traits among students. ‘Scientific interest’ emerged as the best predictor of scientific attitude in intent as well as action. ‘Science achievement’ contributes to the prediction of scientific attitude in action. Three personality traits namely; pessimist, tolerant and analytical emerged as the predictors of scientific attitude in intent while planned and alienated traits contributed to the prediction of scientific attitude in action.